Self-esteem: A Systematic Comparison between Teachers and Trainees in Physical Education and Sports - Aouani, Hajer; Amara, Sofiene (Advances in Social Sciences Research Journal, 2024)
Background: Self-esteem is considered a multidimensional strategy for coping with various complex situations. There are conflicting results regarding the effect of years of experience on dimensions of self-esteem among physical education teachers and trainees. Our study aims to examine the relationship between overall self-esteem in physical education teachers and trainees, and seniority at work. Objectives: In this study, we compared self-esteem between trainees and physical education teachers. Methods: Two hundred sixty individuals (140 young trainees, 120 qualified teachers) participated in this study. They were classified according to their years of experience (1-2 years and 2-5 years). All participants completed Rosenberg’s global self-esteem questionnaire to assess parameters of self-esteem. Results: Physical education teachers had significantly higher values in all dimensions of global self-esteem (GSE) (all, P < 0.001). The comparison between years of experience revealed that as the number of years increases, overall self-esteem (GSE) also increases among physical education teachers. Conclusions: Based on the results from the current study, we conclude that seniority can be considered a key factor in developing levels of self-esteem among physical education teachers and contributes to a better perception of parameters related to global self-esteem (GSE).